MicroRNA-223 Enhances Radiation Sensitivity of U87MG Cells In Vitro and In Vivo by Targeting Ataxia Telangiectasia Mutated - Liang, Liping; Zhu, Ji; Zaorsky, Nicholas G.; Deng, Yun; Wu, Xingzhong; Liu, Yong; Liu, Fangqi; Cai, Guoxiang; Gu, Weilie; Shen, Lijun; Zhang, Zhen (International journal of radiation oncology, biology, physics, 2014)
Ataxia telangiectasia mutated (ATM) protein is important in the DNA damage response because it repairs radiation-induced damage in cancers. We examined the effect of microRNA-223 (miR-223), a regulator of ATM expression, on radiation sensitivity of cancer cells. Human embryonic kidney 293 T (293T) cells were infected with pLL3.7-miR-223 plasmid to generate the pLL3.7-miR-223 and -empty virus (EV) lentivirus (miR-223 and EV). A dual luciferase assay in which the reporter contained wild-type 3′ untranslated region (UTR) of ATM was performed. U87MG cells were infected with miR-223 or EV to establish the overexpressed stable cell lines (U87-223 or U87-EV, respectively). Cells were irradiated in vitro, and dose enhancement ratios at 2 Gy (DER2) were calculated. Hind legs of BALB/c athymic mice were injected with U87-223 or U87-EV cells; after 2 weeks, half of the tumors were irradiated. Tumor volumes were tracked for a total of 5 weeks. The dual luciferase reporter assay showed a significant reduction in luciferase activity of 293T cells cotransfected with miR-223 and the ATM 3′UTR compared to that in EV control. Overexpression of miR-223 in U87MG cells showed that ATM expression was significantly downregulated in the U87-223 cells compared to that in U87-EV (ATM/β-actin mRNA 1.0 vs 1.5, P<.05). U87-223 cells were hypersensitive to radiation compared to U87-EV cells in vitro (DER2 = 1.32, P<.01). Mice injected with miR-223-expressing tumors had almost the same tumors after 3 weeks (1.5 cm3 vs 1.7 cm3). However, irradiation significantly decreased tumor size in miR-223-expressing tumors compared to those in controls (0.033 cm3 vs 0.829 cm3). miR-223 overexpression downregulates ATM expression and sensitizes U87 cells to radiation in vitro and in vivo. MicroRNA-223 may be a novel cancer-targeting therapy, although its cancer- and patient-specific roles are currently undefined.